2013
DOI: 10.1175/mwr-d-12-00056.1
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of the Goshen County, Wyoming, Tornado on 5 June 2009 during VORTEX2

Abstract: The genesis of a strong and long-lived tornado observed during the second Verification of the Origins of Rotation in Tornadoes Experiment (VORTEX2) in Goshen County, Wyoming, on 5 June 2009 is studied. Mobile radar, mobile mesonet, rawinsonde, and photographic data are used to produce an integrated analysis of the evolution of the wind, precipitation, and thermodynamic fields in the parent supercell to deduce the processes that resulted in tornadogenesis. Several minutes prior to tornadogenesis, the rear-flank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 58 publications
14
56
0
Order By: Relevance
“…4 and 5) emanating from intense downdrafts. The leading edges of these horizontal momentum surges are often referred to as secondary rear-flank gust fronts (SRFGF), which are known to accompany the intensification of nearground vertical vorticity also in observed storms (Marquis et al 2008;Kosiba et al 2013). Adlerman et al (1999) also identified outflow trajectories in their Del City simulation (in addition to trajectories originating east of the rear-flank gust front, which were considered error prone; see also Dahl et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 and 5) emanating from intense downdrafts. The leading edges of these horizontal momentum surges are often referred to as secondary rear-flank gust fronts (SRFGF), which are known to accompany the intensification of nearground vertical vorticity also in observed storms (Marquis et al 2008;Kosiba et al 2013). Adlerman et al (1999) also identified outflow trajectories in their Del City simulation (in addition to trajectories originating east of the rear-flank gust front, which were considered error prone; see also Dahl et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The development of rotation at ground level, 1 on the other hand, cannot be achieved by mere upward tilting of initially horizontal vortex lines, but a downdraft is required, as discussed by Davies-Jones (1982), DaviesJones and Brooks (1993), Walko (1993), Markowski and Richardson (2010), and Davies-Jones and Markowski (2013). The reason is that an initially horizontal nearground vortex line is lifted away from the surface as it is reoriented into the vertical at the updraft edge.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of convergence by rearflank downdrafts or internal cold-pool air surges within tornadic supercells has been documented by radar observational studies (e.g., Lemon and Doswell 1979;Marquis et al 2008;Lee et al 2012). Tornadogenesis and tornado maintenance have also been found in close relationship with intensifying downdrafts (Marquis et al 2012;Kosiba et al 2013).…”
Section: Downdrafts and MV Developmentmentioning
confidence: 94%
“…In the other two cases, an EF2 tornado on 5 June 2009 in Goshen County, Wyoming (e.g., Wakimoto et al 2011Wakimoto et al , 2012Markowski et al 2012a,b;Atkins et al 2012;Wurman et al 2013;Kosiba et al 2013;French et al 2013French et al , 2014, and an EF1 tornado on 19 May 2010 near FIG. 10.…”
Section: February 2015mentioning
confidence: 97%